Construtos de loucura no cinema contemporâneo: um olhar tecnocultural sobre a insanidade a partir de Coringa (2019) - Aurich, Amerian (Universidade do Vale do Rio dos Sinos, 2022)
This research analyzes the construction of madness in contemporary cinema through the cinematographic work Joker (2019), by American director Todd Phillips. As a main objective, the study seeks to understand how madness, thought of as a technocultural construct, is updated in technical images in contemporary cinema. For that, relations with the theories gathered in a bibliographic review from authors such as Vilém Flusser (2002), Serguei Eisenstein (2002), Michel Chion (2011), Gustavo Fischer (2013), Michel Foucault (1996, 2006 e 2019), Suzana Kilpp (2002, 2007 e 2010) and Ana da Rosa (2019). The theoretical-methodological procedures used in the development of the analysis are essentially based on the works of Walter Benjamin and are composed of flânerie, collections and constellations (dialectical images). Throughout the research, it was observed that cinema is increasingly being built as a “beyond the screen” extension and from this relation established between “in and out” the cinematographic work, through the film Joker and its unfolding in a network, collections were defined, which brought together fragments by affinities, and two main constellations called “So this is it, are you crazy?!”: Building madness through masks, laughter and dances” and “Is it just me, or is the world getting crazier?”: Violence, protest, isolation and disorder in the construction of insanity”; from these constellations, it was identified that the images “talk” about madness and about the madness of the images themselves.
Keywords: Loucura; Cinema; Coringa; Tecnocultura; Comunicação; Madness; Joker; Technoculture; Communication; ACCNPQ::Ciências Sociais Aplicadas::Comunicação